2019
DOI: 10.2217/cns-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly fotemustine schedule for recurrent glioblastoma in the elderly: activity and toxicity assessment of a multicenter study

Abstract: Aim: To assess the efficacy and safety of alternative fotemustine administration schedule in elderly patients with recurrent glioblastoma. Patients & methods: Patients aged >65 years with recurrent glioblastoma received fotemustine (80 mg/m2; days 1, 15, 30, 45 and 60, and subsequently every 4 weeks). Primary end point was progression-free survival (PFS) rate at 6 months. Main secondary end point was safety. Results: 58 patients were enrolled at two centers. PFS at 6 months was 47% (27 patients) and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Several studies[ 1 , 19 , 33 ] have reported that FTM is a valuable therapeutic option for elderly patients with rGBM. Paccapelo et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies[ 1 , 19 , 33 ] have reported that FTM is a valuable therapeutic option for elderly patients with rGBM. Paccapelo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Addeo et al [1] Original 2019 58 >65 Chemotherapy with fotemustine is effective and safe treatment 7.…”
Section: No Of Casesmentioning
confidence: 99%
See 2 more Smart Citations
“… 26 Procarbazine was found to be less effective than temozolomide in a randomized trial. 22 Fotemustine, a third-generation intravenous nitrosourea with lower rates of thrombocytopenia, 27 , 28 is used in several countries at different schedules.…”
Section: Currently Approved Treatments For Recurrent Glioblastomamentioning
confidence: 99%